FARM INFORMATION NEED ASSESSMENT THROUGH DIGITAL MEANS - K, Kamaleswaran; R, Rajasekaran; M.Sathaiah; T.Ragunathan (ShodhKosh: Journal of Visual and Performing Arts, 2026)
The adoption rate of digital technologies in agriculture is increasing at an exponential pace. Therefore, this study aims to examine the information needs of farmers, the digital platforms they utilizing, their perceptions of the effectiveness of advisory services offered by these platforms, the challenges they fare while adopting such services, and their suggestions for improvement. A total number of 120 farmers were interviewed using a structured interview schedule and the data were analyzed using descriptive statistics and principal component analysis (PCA). The findings indicate that farmers have a greater need for information related to soil testing and fertility management, crop production practices and weed management. Factor analysis categorized these needs into five underlying dimensions climate and crop production information, market-oriented production information, institutional and financial support information, soil and input management information, and digital market information. The analysis of digital information sources revealed two dominant usage patterns: one associated with formal platforms, such as government portals, weather applications, mobile-based agricultural apps, and another associated with interactive platforms, including YouTube, social media page and webinars. This study underscores the importance of strengthening a localized, credible, and farmer-oriented digital extension system to enhance agricultural productivity and income.